Global Screening of Salmonella enterica Serovar Typhimurium Genes for Desiccation Survival - Mandal, Rabindra K.; Kwon, Young M. (Frontiers in Microbiology, 2017)
Salmonella spp., one of the most common foodborne bacterial pathogens, has the ability to survive under desiccation conditions in foods and food processing facilities for years. This raises the concerns of Salmonella infection in humans associated with low water activity foods. Salmonella responds to desiccation stress via complex pathways involving immediate physiological actions as well as coordinated genetic responses. However, the exact mechanisms of Salmonella to resist desiccation stress remain to be fully elucidated. In this study, we screened a genome-saturating transposon (Tn5) library of Salmonella Typhimurium (S. Typhimurium) 14028s under the in vitro desiccation stress using transposon sequencing (Tn-seq). We identified 61 genes and 6 intergenic regions required to overcome desiccation stress. Salmonella desiccation resistance genes were mostly related to energy production and conversion; cell wall/membrane/envelope biogenesis; inorganic ion transport and metabolism; regulation of biological process; DNA metabolic process; ABC transporters; and two component system. More than 20% of the Salmonella desiccation resistance genes encode either putative or hypothetical proteins. Phenotypic evaluation of 12 single gene knockout mutants showed 3 mutants (atpH, atpG, and corA) had significantly (p<0.02) reduced survival as compared to the wild type during desiccation survival. Thus, our study provided new insights into the molecular mechanisms utilized by Salmonella for survival against desiccation stress. The findings might be further exploited to develop effective control strategies against Salmonella contamination in low water activity foods and food processing facilities.